MUE555 : Curriculum development in music education / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course exposes students to the various terms, principles, taxonomies, models and dimensions of curriculum construct, development and evaluation. Students also review the current national school music curriculum including the new school curriculum for performing arts. They study aspects of quality assurance in accordance to programme accreditation requirements of the Malaysian Qualifications Agency. Students apply knowledge to produce tangible music curriculum products premised on outcome based education and student centred learning.